Implementation Of Pedagogical Competencies Of Love Curriculum At The Madani Ikhwanul Hasanah Pesantren - Ihwal Syahwaludin; Wawan Arbeni (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the implementation of teachers' pedagogical competencies in integrating the values of the love curriculum at the Madani Ikhwanul Hasanah Islamic boarding school. The study uses a descriptive qualitative approach with a case study. The data sources consisted of in-depth interviews, observations, and documentation obtained from teachers, pesantren administrators, and students. The data analysis technique used the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. The results of the study indicate that although teachers' pedagogical competencies are adequate, there are challenges in applying the values of the love curriculum. Some teachers admitted that they had difficulty integrating the value of love into their teaching due to limited resources and time. The application of the love curriculum at the pesantren has a positive impact on the character building of students, but it still needs to be strengthened with more structured training for teachers.